Analisis Pengendalian Kualitas Produk Plastik Menggunakan Metode Six Sigma Dan Kaizen (Studi Kasus: PT Kusuma Mulia Plasindo Infitex) - Niken Rahmawati; Ari Zaqi Alfaritsy (Pusat Riset dan Inovasi Nasional, 2023)
PT Kusuma Mulia Plasindo Infitex is a company engaged in the manufacturing sector that produces polypropylene and HD (Hight density Polyethylene) plastic products. The problem that occurred at PT Kusuma Mulia Plasindo Infitex was that the number of defective products on HD plastic products of 98,327 kg contained 4,194 kg of defective products. The purpose of this study is to determine the factors that cause defects and suggestions for improvements to minimize defective products. This study uses the six sigma method which is useful for finding the root causes of problems that are adjusted to the characteristics of the data they have. The 5 stages of six sigma are DMAIC(define, measure, analyze, improve, control) and kaizen is the Five M-Checklist. So from the results of data processing, the value is obtained in the form of DPMO 8393.048 and a sigma value of 2.49. Proposed improvements include providing training in plastic welding, providing additional 5-10 minute breaks and supervision while working. Perform routine machine maintenance every month and cleaning every day. Adding ventilation and blowers in the production room. Carry out the production process according to the existing SOP at the company, especially in mixing materials according to the SOP for raw materials that have been made by the company.